A genome-wide association study of coat color in Chinese Rex rabbits - Zhang, Kai; Wang, Guozhi; Wang, Lihuan; Wen, Bin; Fu, Xiangchao; Liu, Ning; Yu, Zhiju; Jian, Wensu; Guo, Xiaolin; Liu, Hanzhong; Chen, Shi-Yi (Frontiers in Veterinary Science, 2023)
Coat colour is an important phenotypic characteristic of domestic rabbit (Oryctolagus cuniculus) and has specific economic importance in Rex rabbit industry. The coat colours are considerably varied among different populations of rabbits, for which several causal genes have been well studied. Nevertheless, the candidate genes affecting the coat colour variation in Chinese Rex rabbits remained to be investigated.In this study, we collected blood samples of 250 Chinese Rex rabbits with six different coat colours. We performed genome sequencing using a restriction site-associated DNA sequencing approach. A total of 91,546 single nucleotide polymorphisms (SNPs) evenly distributed among 21 autosomes were obtained. The genome-wide association studies (GWAS) were performed using mixed linear model, in which the individual polygenic effect was fitted as random effect. We detected 24 significant SNPs in total that were located within a genomic region on chromosome 4 (OCU4). After re-fitting the most significant SNP (OCU4:13,434,448 and P = 1.31e-12) as a covariate, another near-significant SNP (OCU4:11,344,946 and P = 7.03e-07) was still present. Hence, this 2.1 Mb genomic region located between the two significant SNPs is significantly associated with the coat colours in Chinese Rex rabbits. Within this region, the well-studied coat colour-associated gene agouti signaling protein (ASIP) is located. Furthermore, low genetic differentiations among the six coat colour varieties were also revealed. In conclusion, our results confirmed that ASIP is a putative causal gene affecting the coat colour variation in Chinese Rex rabbits.